Clay mineralogy of the upper Miocene-Pliocene red clay from the central Chinese Loess Plateau and its paleoclimate implications. (30th June 2020) - Wang, Qiansuo; Song, Yougui; Li, Yue
Abstract: Study of clay mineral is one of effective methods for reconstruction of the paleoclimate and paleoenvironment. Here we represent clay mineral records from an upper Miocene–Pliocene red clay succession in the central Chinese Loess Plateau (CLP). On the basis of the existing age model, we employ X-ray diffraction and scanning electron microscopy to carry out clay mineral analyses, the results indicated that illite was the dominant clay mineral and the contents of smectite, chlorite and kaolinite were minor. From the analysis of contents of clay minerals, illite crystallinity, illite 5 Å/10 Å, smectite/(illite+chlorite) ratio, magnetic susceptibility, summer monsoon intensity and deep-sea δ 18 O values, the paleoclimatic evolution between 7.5 and 2.6 Ma can be divided into three intervals: interval I, from 7.5 to 6.9 Ma, it was cool and dry; interval II, from 6.9 to 4.1 Ma, was cool-warm oscillations; interval III, from 4.1 to 2.6 Ma, was significantly warm and humid stage of the seasonal climate conditions. The proxy records display a large amplitude transition in the later interval III, from 2.8 to 2.6 Ma, which implied an abrupt climate and environment variability. Through comparison the local and global paleoclimatic records, we found that clay minerals reflect regional paleoclimatic change superimposing global climatic records during the late Miocene–Pliocene period. We conclude that the regional tectonic activity and global cooling had affected East Asia Monsoon, which was characterized by the different temperature and precipitation in the central CLP. Highlights: Clay minerals of Chaona red clay belong to detrital origin. The paleoclimate evolution recorded by clay minerals between 7.5 and 2.6 Ma experienced cool and dry, cool-warm oscillations and warm and humid three intervals. The regional tectonic activity and global cooling have affected East Asia Monsoon, which was characterized by the different temperature and precipitation in the central CLP. Fee waived: n Embargo type: None Embargo Date time zone: 0:00.